Harnessing the Foreign Body Reaction in Marginal Mass Device-less Subcutaneous Islet Transplantation in Mice. Issue 7 (July 2016) - Pepper, Andrew R.; Pawlick, Rena; Bruni, Antonio; Gala-Lopez, Boris; Wink, John; Rafiei, Yasmin; Bral, Mariusz; Abualhassan, Nasser; Shapiro, A. M. James
Abstract : Background: Islet transplantation is a successful β-cell replacement therapy for selected patients with type 1 diabetes mellitus. However, despite early insulin independence, long-term graft attrition gradually reverts recipients to exogenous insulin dependency. Undoubtedly, as insulin producing stem cell therapies progress, a transplant site that is retrievable is desirable. This prerequisite is currently incompatible with intrahepatic islet transplantation. Herein, we evaluate the functional capacity of a prevascularized subcutaneous site to accommodate marginal islet mass transplantation in mice. Methods: Syngeneic mouse islets (150) were transplanted either under the kidney capsule (KC), into a prevascularized subcutaneous device-less (DL) site, or into the unmodified subcutaneous (SC) tissue. The DL site was created 4 weeks before diabetes induction and islet transplantation through the transient placement of a 5-Fr vascular catheter. Recipient mice were monitored for glycemic control and intraperitoneal glucose tolerance. Results: A marginal islet mass transplanted into the DL site routinely reversed diabetes (n = 13 of 18) whereas all SC islet recipients failed to restore glycemic control (n = 0 of 10, P < 0.01, log-rank). As anticipated, nearly all islet-KC mice (n = 15 of 16) became euglycemic posttransplant. The DL recipients' glucose profiles were comparable to KC islet grafts, postintrapertioneal glucose tolerance testing, whereas SC recipients remained hyperglycemic postglucose challenge. All normoglycemic mice maintained graft function for 100 days until graft retrieval. DL and KC islet grafts stained positively for insulin, microvessels, and a collagen scaffold. Conclusions: The device-less prevascularized approach supports marginal mass islet engraftment in mice. Abstract : By subcutaneously implanting a medically approved vascular catheter subcutaneously into the lower left quadrant of C57BL/6 mice to create a device-less prevascularized space, Pepper et al report superior islet engraftment compared to the kidney subcapsular or unmodified subcutaneous space.